How to Price Catastrophe Bonds for Sustainable Earthquake Funding? A Systematic Review of the Pricing Framework - Riza Andrian Ibrahim; Sukono; Herlina Napitupulu; Rose Irnawaty Ibrahim (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Indexed by WOS/Scopus/ERA